"Here, Man Is Nothing!": Gender and Policy in an Asylum Context. (October 2015) - Griffiths, Melanie
In policy terms, "genuine" refugees are conceptualized as vulnerable, coerced victims, an image that does not reflect the realities of most male refugees and asylum seekers. Not only does the image conflict with dominant forms of masculinity, but as refused asylum seekers have their purported vulnerability rejected and honesty challenged as part of having their claim refused, there is an implicit conclusion that they are deceptive, opportunistic, or even criminal. The emblematic "bogus asylum seeker" figure is generally imagined to be male and is associated with gendered suspicions and expectations regarding agency. Concurrently, however, the asylum system operates various emasculating tendencies. Using testimonies from male refused asylum seekers, this article explores the interplay of gender and asylum law and policy, examining how individuals understand and negotiate their reconstruction from vulnerable would-be refugee to undeserving "bogus" asylum seeker. Gender is presented as an unspoken but critical dimension of this immigration category.